PREVENTION AND FIGHT AGAINST CRIME IN UZBEKISTAN - Nurbek Safarov (Sciental Journals Publishing, 2025)
This article analyzes the pressing issues of combating offenses and crime in Uzbekistan, the existing challenges, and their possible solutions. It discusses the measures taken to ensure the rule of law, improve the law enforcement system, and prevent crimes in the country. Additionally, it highlights the significance of increasing legal awareness, reforming the penal system, and strengthening preventive measures against crime to ensure public safety. The role of historical science is not only to study the past but also to draw lessons from its experience to solve contemporary issues. The history of combating offenses and crime in Uzbekistan should be studied as one of the crucial periods in ensuring social stability. This article examines the distinctive features of historical periods, past experiences, and their connection with ongoing reforms.
Keywords: Offense, crime, crime prevention, legal reforms, public safety, rule of law, law enforcement agencies, prevention, penal system, social prevention.